Colorimetric Detection Of Heavy Metal Ions Using Silver Nanoparticles Synthesized From Alpinia Galanga - Arzuan, Muhamad Zulhelmi Nor (Universiti Sains Malaysia, 2022)
The metal nanoparticles such as gold (Au), silver (Ag) and copper (Cu) have been extensively utilized as a sensing material for colorimetric detection of metal ions in a solution since they exhibit localized plasmon resonance (LPSR) properties. In the present study, silver nanoparticles (AgNPs) were synthesized from Alpinia galanga plant extract by using biological method and colorimetric sensing properties were investigated by using various type of heavy metal at concentration of 1 mM. Biological synthesis of AgNPs can be considered as more promising alternatives than chemical methods because it is more flexible, environmentally friendly and cost-effective method. Optimization process was conducted to study the effect of plant extract concentration, ratio of plant extract to AgNO3 solution and pH value on the formation and growth of AgNPs. The optimal condition for AgNPs synthesis is plant extract concentration of 10 wt%, ratio of plant extract to AgNO3 solution of 1:5 and pH value near to neutral which is pH 7. Colorimetric detection of heavy metal and sensitivity test then were carried out to determine the ability of AgNPs to detect metal ions in small concentration. From heavy metal colorimetric detection, it can be observed that CuCl2 has the highest difference between the absorbance peak of AgNPs before and after the addition of heavy metals at 0.45475, which also indicates that AgNPs show greater sensitivity towards CuCl2 solution. The result from UV-Vis analysis in the sensitivity test demonstrated that when the concentration of heavy metal solution decreases from 0.8 mM to 0.2 mM, the absorbance peak will increase. The prepared AgNPs was characterized by using UV-Vis spectrophotometry, zeta potential,scanning electron microscopy (SEM) and energy dispersive x-ray (EDX) analysis. The EDX analysis confirmed the presence of silver particles at 61.21 % of weight whereas the morphology of AgNPs were determined by SEM analysis. The nanoparticles were found to have almost spherical morphology from the SEM images. From zeta potential analysis, the nanoparticles proved to have stable colloidal system as it has large negative zeta potential at -39.3 mV.